2020
DOI: 10.1021/acs.molpharmaceut.0c00457
|View full text |Cite
|
Sign up to set email alerts
|

Development of 5D3-DM1: A Novel Anti-Prostate-Specific Membrane Antigen Antibody-Drug Conjugate for PSMA-Positive Prostate Cancer Therapy

Abstract: Prostate cancer (PC) is a potentially high-risk disease and the most common cancer in American men. It is a leading cause of cancer-related deaths in men in the US, second only to lung and bronchus cancer. Advanced and metastatic PC is initially treated with androgen deprivation therapy (ADT), but nearly all cases eventually progress to castrate-resistant prostate cancer (CRPC). CRPC is incurable in the metastatic stage but can be slowed by some conventional chemotherapeutics and second-generation ADT, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…With this protocol, we were able to monitor and quantify the entire PSMA/probe complex formation and endocytosis process in living cells in real-time. By quantifying the effects of different types of endocytosis inhibitors on PSMA-mediated endocytosis, we confirmed that the clathrin-dependent endocytosis pathway plays the most important role in the endocytosis of PSMA 53 , 54 , while the contribution of the caveolin-dependent and micropinocytosis pathway is quite limited. That is consistent with the established results that most transmembrane receptors are internalized via a clathrin-dependent mechanism, as recently shown by Matthias et al, who did so using stimulated emission depletion (STED) nanoscopy 55 .…”
Section: Discussionmentioning
confidence: 64%
“…With this protocol, we were able to monitor and quantify the entire PSMA/probe complex formation and endocytosis process in living cells in real-time. By quantifying the effects of different types of endocytosis inhibitors on PSMA-mediated endocytosis, we confirmed that the clathrin-dependent endocytosis pathway plays the most important role in the endocytosis of PSMA 53 , 54 , while the contribution of the caveolin-dependent and micropinocytosis pathway is quite limited. That is consistent with the established results that most transmembrane receptors are internalized via a clathrin-dependent mechanism, as recently shown by Matthias et al, who did so using stimulated emission depletion (STED) nanoscopy 55 .…”
Section: Discussionmentioning
confidence: 64%
“…Similarly to other PSMA-specific antibody fragments [72,76], we observed signal originated from 5D3 conjugates in kidneys and liver that is connected with metabolism and clearance of recombinant proteins. Described distribution should be carefully followed particularly in future development of radionuclide or cytotoxic drug 5D3 conjugates because of potential risk of kidney toxicity [45]. The behavior of original 5D3 mAb in long time lapse was also similar to other high-affinity mouse antibodies [77], as the mAb revealed the peak of accumulation at days 4-6 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we exploit the superior features of our newly developed 5D3 mAb, including sub-nanomolar affinity and a high specificity for native PSMA [43]. These characteristics make the 5D3 mAb particularly suitable for in vivo applications [44][45][46]. Here, we cloned, heterologously expressed, purified, and characterized engineered scFv and Fab fragments of 5D3.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation was partially overcome by the development of another anti-PSMA antibody, J591, that binds extracellular epitopes of PSMA, and was largely used in preclinical and clinical trials (ClinicalTrials.gov Identifier: NCT00195039; NCT02410577). Other mAbs directed to PSMA extracellular epitopes, as well as their conjugates, are being evaluated in a variety of experimental and preclinical models [ 23 , 24 , 25 ], but only IgGD2B [ 26 ], similarly to J591 [ 27 ], has been extensively characterized, demonstrating low tumor-to-blood ratios that can occur owing to relatively slow clearance of intact antibodies compared with fragments [ 28 ]. Different groups analyzed IgGD2B tumor-targeting capacity ( Table 1 , refs.…”
Section: Psma-targeted Diagnosis/therapy With Monoclonal Antibodiesmentioning
confidence: 99%